VII. NIH TOOLBOX COGNITION BATTERY (CB): FACTOR STRUCTURE FOR 3 TO 15 YEAR OLDS. Issue 4 (16th August 2013) - Mungas, Dan; Widaman, Keith; Zelazo, Philip David; Tulsky, David; Heaton, Robert K.; Slotkin, Jerry; Blitz, David L.; Gershon, Richard C.
ABSTRACT Confirmatory factor analysis was used the evaluate the dimensional structure underlying the NIH Toolbox Cognition Battery (CB) and the measures chosen to serve as concurrent validity criteria for the NIH Toolbox CB. These results were used to evaluate the convergent and discriminant validity of the CB in children ranging from 3 to 15 years of age. Results were evaluated separately for a 3‐ to 6‐year‐old group and a 8‐ to 15‐year‐old group because different validation measures were used in these age groups. Three distinct dimensions were found for the 3‐ to 6‐year‐old group: Vocabulary, Reading, and Fluid Abilities. Five dimensions were found for 8–15 year olds: Vocabulary, Reading, Episodic Memory, Working Memory, and Executive Function/Processing Speed. CB measures and their validation analogues consistently defined common factors in a pattern that broadly supported the convergent and discriminant validity of the CB, but results showed higher intercorrelation and less differentiation of cognitive dimensions in younger than in older children and in older children compared with adults. Age was strongly related to the cognitive dimensions underlying test performance in both groups of children and results are consistent with broader literature showing increasing differentiation of cognitive abilities associated with the rapid brain development that occurs from early childhood into adulthood.